$f(0)=1;\ f(-1)=-3;\ f(-2)=16;\ f(-3)=-3Ta có f(-3).f(-2)=-3 \Rightarrow tồn tại ít nhất 1 nghiệm x_0 \in (-3;\ -2) f(-2).f(-1) = -16 <0 \Rightarrow tồn tại ít nhất 1 nghiệm x_1 \in (-2;\ -1)$$f(-1). f(0) =-3 <0 \Rightarrow $ tồn tại ít nhất 1 nghiệm $x_2 \in (-1;\ 0)$Vậy pt có 3 nghiệm phân biệt
$f(0)=1;\ f(-1)=-3;\ f(-2)=16;\ f(-
4)=-3
Ta có f(-
4).f(-2)=-3 \Rightarrow
tồn tại ít nhất 1 nghiệm x_0 \in (-
4;\ -2)
f(-2).f(-1) = -16 <0 \Rightarrow
tồn tại ít nhất 1 nghiệm x_1 \in (-2;\ -1)$$f(-1). f(0) =-3 <0 \Rightarrow $ tồn tại ít nhất 1 nghiệm $x_2 \in (-1;\ 0)$Vậy pt có 3 nghiệm phân biệt